Penerapan Strategi Marketing Sosial dalam Membentuk Kesadaran Mahasiswa - E. B., Gita Aprinta; Syamsiah, Sri; L., Hernofika (Universitas Semarang, 2017)
Social Marketing Strategy toward Brand Awareness of Students Habit of FTIK Students, Universitas Semarang. There is a problem regarding student s habits of recycle habit in the campus environment, that became worst and impact to campus environment. This research tries to solve the problem by using social marketing strategy methods. Social marketing seeks to develop and integrate marketing concepts with other approaches to influence behaviors. Social marketing can be used as a problem solving by integrated communication principle and marketing techniques. This research tries to use social marketing in formulating some strategies to solve those habits problem by developing students s social awareness in order to change their bad habit in garbage throwing. The results shows that social marketing strategy start from 4P components to fulfill awareness pyramid in brand recognition level. It means that students will act if there is a reminders from their peers group.